The Role of Product Design in Purchase Intention: Mediating Effects of eWOM Intention and Hedonic Value in Social Commerce - Yulinda L. Ismail; Asriani Asriani; Jeni Kamase (Advances in Business & Industrial Marketing Research, 2026)
Purpose: This study examines the effect of product design on purchase intention in social commerce, particularly TikTok Shop, by analyzing the mediating roles of hedonic value and eWOM intention. Research Method: A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed. Data were collected from TikTok users through purposive sampling. The constructs measured include product design, hedonic value, eWOM intention, and purchase intention, analyzed using SmartPLS. Results and Discussion: The results show that product design significantly influences both hedonic value and eWOM intention. Both variables significantly affect purchase intention, with eWOM intention showing a stronger effect. The direct effect of product design on purchase intention is not significant when mediators are included but becomes significant when excluded, indicating full mediation. This suggests that product design influences purchase intention indirectly through emotional and social mechanisms, with social influence playing a more dominant role. Implications: The findings highlight the importance of integrating emotional and social strategies in social commerce. Businesses should focus on encouraging user interaction and content sharing rather than relying solely on visual appeal. Originality: This study offers a novel integrated model demonstrating that eWOM intention is a more dominant mediator than hedonic value in visual-based social commerce environments.